PESANTREN RELIGIOUS PARADIGM: AQEEDAH, PLURALITY, AND JIHAD - Arifinsyah, Arifinsyah; Ryandi, Ryandi; Manshuruddin, Manshuruddin (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The purpose of this study is to describe analytically pesantren religious paradigm in North Sumatera, by tracing their teaching of Aqeedah, plurality, and jihad. The study focuses on two pesantren which are considered as the largest pesantren, they are MusthafawiyahPurbabaruMandailing Natal and RaudhahHasanah Medan. Quantitatively, both pesantren have more than 1000 entries, which come from various regions of Sumatera, and even outside it. The former was the oldest traditional (salafiyah) pesantren in North Sumatera while the latter was one of the earliest pesantren in which the system refers to the modernity of Pondok Modern Darussalam Gontor. The method is qualitative research. Interview, observation, and document analysis were used to collect data. This study has found that two pesantren educated their students with moderate values. It can be seen from: First, their Aqeedah teaching mostly refers to the theological school of Asy?ari and Maturity. These two schools of theology are considered as a moderate school by contemporary moslem scholars, and as majority school of ummah in Indonesia. Second, plurality according to them is a necessity. Moslem has to seek for peaceful co-existence and mutual tolerance between the people of different religions and cultures. Third, the term jihad to them is not only in a physical war but also in intellectual, against lust and doing creative work in society.